Highly sensitive LC-MS/MS method to estimate doxepin and its metabolite nordoxepin in human plasma for a bioequivalence study - Nirav P. Patel; Mallika Sanyal; Naveen Sharma; Dinesh S. Patel; Pranav S. Shrivastav; Bhavin N. Patel (Elsevier, 2018)
A selective, sensitive and rugged liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay has been developed for the simultaneous determination of doxepin (Dox) and its pharmacologically active metabolite, nordoxepin (NDox) in human plasma. The analytes and their internal standards (IS) were extracted from 500 µL of human plasma by liquid-liquid extraction using methyl tert-butyl ether. Chromatographic separation was achieved on Hypurity C8 column (100 mm × 4.6 mm, 5 µm) using a mixture of acetonitrile-methanol (95:5, v/v) and 2.0 mM ammonium formate in 93:7 (v/v) ratio. Detection was accomplished by tandem mass spectrometry in the positive ionization and multiple reaction monitoring acquisition mode. The protonated precursor to product ion transitions studied for Dox, NDox, and their corresponding ISs, propranolol and desipramine, were m/z 280.1→107.0, 266.0 →107.0, 260.1→116.1 and 267.1→72.1, respectively. A linear dynamic range of 15.0-3900 pg/mL for Dox and 5.00-1300 pg/mL for NDox was established with mean correlation coefficient (r2) of 0.9991 and 0.9993, respectively. The extraction recovery ranged from 86.6%-90.4% and 88.0%-99.1% for Dox and NDox, respectively. The intra-batch and inter-batch precision (% CV) across quality control levels was ≤ 8.3% for both the analytes. Stability evaluated under different storage conditions showed no evidence of degradation and the % change in stability samples compared to nominal concentration ranged from 4.7% to 12.3%. The method was successfully applied to a bioequivalence study of 6 mg doxepin hydrochloride orally disintegrating tablet in 41 healthy Indian subjects under fasting and fed conditions. Keywords: Doxepin, Nordoxepin, LC-MS/MS, Liquid-liquid extraction, Human plasma, Bioequivalence study